Nigerian Historiography Through the Eyes of Nigerian Diaspora Historians: Issues of Decolonisation and Functionality of Knowledge - Olugbodi, Oladipupo (African historical review, 2024)
This study scrutinises the subjects of knowledge decolonisation and functionality in Nigerian historiography through the lens of Nigerian diaspora historians, focusing on the perspectives of key figures such as Toyin Falola and Saheed Aderinto in Nigeria, Nationalism and Writing History and Jeremiah Dibua in "The Idol, Its Worshippers, and the Crisis of Relevance of Historical Scholarship in Nigeria." By studying the perspectives of these Nigerian scholars, the connection of the subjects of decolonisation and functionality are brought to the fore, laying the foundation for an analysis of how historical knowledge can be further decolonised and functional to the needs of society. The study adopted a historical approach and made use of primary and secondary sources. The bulk of the analysis in this study was drawn from the two works stated above, supplemented by other works. This study is a qualitative historiographical survey. The study found that while Nigerian historians have achieved success in knowledge decolonisation, they still need to do more in knowledge functionality through collaborative efforts between home-based and diaspora historians as complete decolonisation of knowledge on Africa cannot be achieved without knowledge functionality. The study concluded that knowledge decolonisation and functionality are important for the growth of historical practice in Nigeria and that Nigerian scholars should increasingly emphasise the subject of knowledge functionality in their historiography and historical practice.